Effects of Non-Protein Nitrogen Sources on In Vitro Rumen Fermentation Characteristics and Microbial Diversity - Zhu, Jinjia; Ren, Ao; Jiao, Jinzhen; Shen, Weijun; Yang, Lingyuan; Zhou, Chuanshe; Tan, Zhiliang (Frontiers in Animal Science, 2022)
The effect of non-protein nitrogen sources on fermentation parameters and microbial diversity was studied using 3 fistula goats as the rumen fluid donors. This study involved 6 fermenters in a replicated 3 × 3 Latin square design with 3 dietary non-protein sources（ammonium chloride A, biuret B, glutamine G）as treatment factors using a dual-flow continuous culture fermentation system. The results showed that the MCP concentration in B group was significantly lower than the other two treatments (P<0.05). There was a significant difference in ammonia nitrogen concentration (P<0.01), being G group > A group > B group. The ratio of acetate to propionate in the G treatment was significantly lower than the other two treatments (P<0.01). The relative abundance of Cyanobacteria, Elusimicrobia and Armatimonadetes was the greatest in the G group, and it was significantly higher than the B group (P<0.05) at phylum level. At the genus level, the relative abundance of Ruminococcus_1 in the A group was significantly higher than that in the B group (P<0.05). In summary, glutamine seemed to shift fermentation pathways from acetate to propionate pathway, and the lower content of MCP and lower relative abundance of the main fiber degradation bacteria Ruminococcus_1 and protein degradation bacteria Prevotellaceae_UCG-001 when supplemented with biuret indicated that biuret was not suitable for dietary protein supplementation as non-protein nitrogen.